Low temperature reduces potato wound formation by inhibiting phenylpropanoid metabolism and fatty acid biosynthesis - Zhang, Jiadi; Yao, Jia; Mao, Linli; Li, Qingpeng; Wang, Lixia; Lin, Qing (Frontiers in Plant Science, 2023)
Potato tubers have the healing capacity to prevent surface water transpiration and pathogen invasion after mechanical damage. Previous research has shown the inability to form healing periderm in potatoes under low temperatures, but the potential mechanism is still unclear. To explore the effects and mechanisms of low-temperature potato healing, wounded potatoes were stored at low temperature (4 °C) and room temperature (22 °C), respectively. In this study, compared with 22 ℃ healing, low temperature reduced the content of hydrogen peroxide, and the down-regulation of StAMY23 inhibited the conversion of starch to sugar, alleviated the degradation of starch, and reduced the content of soluble sugars and sucrose. Meanwhile, inhibition of phenylalanine metabolism by suppression of StPAL1 and St4CL expression reduced lignin accumulation. Low temperature also down-regulated the expression of StKCS6, StFAOH, StGPAT5, and StPrx, causing the lower deposition amount of suberin in wounds of potato tubers. The above results suggested that low temperature led to less wound tissue deposition at the wound surfaces via suppressing phenylpropanoid metabolism and fatty acid biosynthesis in potato tubers.